Univariate and Multivariate Analysis of Tannin-Impregnated Wood Species Using Vibrational Spectroscopy. Issue 4 (April 2014) - Schnabel, Thomas; Musso, Maurizio; Tondi, Gianluca
Vibrational spectroscopy is one of the most powerful tools in polymer science. Three main techniques—Fourier transform infrared spectroscopy (FT-IR), FT-Raman spectroscopy, and FT near-infrared (NIR) spectroscopy—can also be applied to wood science. Here, these three techniques were used to investigate the chemical modification occurring in wood after impregnation with tannin–hexamine preservatives. These spectroscopic techniques have the capacity to detect the externally added tannin. FT-IR has very strong sensitivity to the aromatic peak at around 1610 cm −1 in the tannin-treated samples, whereas FT-Raman reflects the peak at around 1600 cm −1 for the externally added tannin. This high efficacy in distinguishing chemical features was demonstrated in univariate analysis and confirmed via cluster analysis. Conversely, the results of the NIR measurements show noticeable sensitivity for small differences. For this technique, multivariate analysis is required and with this chemometric tool, it is also possible to predict the concentration of tannin on the surface.